Optimal Linear Attack on Cyber Physical Systems With Multiplicative Noise - Fangfei Li; Chao Yang; Yang Tang (IEEE Access, 2018)
Cyber-security issues have generated a surge of interests in recent years. In order to understand the behavior of potential attackers, one needs to investigate the malicious attacks from the viewpoint of an invader. In this paper, an optimal linear attack is considered for a cyber physical system with multiplicative noise. A linear attack is proposed first and the feasibility of launching a successful attack without being detected is analyzed. In addition, the estimation error covariance is derived under the proposed linear attack. Furthermore, the optimal attack strategy is transformed into difference of convex programming problems. Finally, a simulation example is presented to demonstrate the obtained results.